The Role Of Macronutrient Intake On Increasing Vo?Max In Athletic Learning In Schools: A Systematic Literature Review - Ishak Bachtiar (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
Background: VO?max is one of the most important indicators of cardiorespiratory fitness and plays a crucial role in supporting students’ performance during athletics learning in schools. Adequate macronutrient intake, including carbohydrates, proteins, and fats, is essential for energy production, physiological adaptation, and aerobic endurance development. However, evidence regarding the role of macronutrient intake in improving VO?max among school-aged students remains fragmented. Objective: This study aimed to systematically review and synthesize conceptual and empirical evidence regarding the role of macronutrient intake in enhancing VO?max during school-based athletics learning. Methods: A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Literature was retrieved from Scopus, Web of Science, PubMed, ScienceDirect, Google Scholar, SINTA, and Garuda databases. From 186 identified articles, 25 studies published between 2016 and 2025 met the inclusion criteria and were analyzed. Data were synthesized using a narrative thematic approach. Results: The findings revealed that 88% of the reviewed studies reported a positive relationship between adequate macronutrient intake and VO?max improvement. Carbohydrates showed the strongest contribution, with 92% of studies demonstrating significant benefits for aerobic capacity, followed by protein (84%) and fat (72%). Intervention studies reported VO?max improvements ranging from 11% to 16% when balanced macronutrient intake was combined with structured athletics training. Conceptually, the findings support the Energy Availability Theory, Glycogen Depletion Theory, Muscle Protein Synthesis Theory, and Fat Oxidation Theory. Conclusion: Adequate macronutrient intake is a key determinant of VO?max development and cardiorespiratory fitness in school athletics learning. Integrating nutrition education with athletics programs can optimize students’ physical fitness, learning participation, and overall health outcomes.